PENGELOLAAN PENGUNJUNG ASIA FARM PEKANBARU - Rizky Armanda; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This paper aims to provide information and understanding of the impact of tourism on the economic sector, social and cultural life, and the environment. Globally, tourism can be said to be one of the leading sectors that make a major contribution to global GDP. It is not surprising that many countries depend on tourism for their economy and many countries are trying to develop their tourism potential. Rapid development and massive negative and positive impacts on the economic sector, social and cultural life, and the environment. The bad impact of tourism must be comfortable and well managed by the government, tourism actors, and the community. One that can be applied is visitor management which is an administrative step to preserve the environment, social culture, and economy without tourist satisfaction. visitor management is carried out by balancing the needs of tourists, the needs of the community, the needs of tourism actors, and the environmental situation. The implementation of visitor management leads to sustainable tourism. Keywords :Visitor Management, Tourism Object, Management